Pengaruh Pertumbuhan Penduduk, Inflasi, Tingkat Pendidikan dan Zakat Terhadap Tingkat Kemiskinan di Kota Samarinda Tahun 2016-2022 - Saputri, Inandha; Nurzaroni, Akhmad; Fadhilah, Nurul (Borneo Islamic Finance and Economics Journal, 2023)
For Indonesia, the problem of poverty is not new, almost every period of government has had poverty problems, one of them is Samarinda city. Even though the third lowest poverty rate after Balikpapan and Bontang, Samarinda City has the second highest number of impoverished people in East Kalimantan and a population in extreme poverty. The poverty rate can be influenced by various factors, population growth and inflation, but the poverty rate can be overcome by the level of education and zakat. The objective of this study is to determine the partial and simultaneous effect of population growth, inflation, education level, and zakat on the poverty rate in Samarinda City in 2016-2022. Multiple linear regression analysis techniques using the SPSS 23 programme used as the data analysis technique in this study. The result of this study show that: (1) The population growth partially has no effect on the poverty rate. (2) The inflation partially has no effect on the poverty rate. (3) the education level partial does not have a significant effect on the poverty rate. (4) the zakat partially does not have a significant effect on the poverty rate. (5) The population growth, inflation, level of education, and zakat simultaneously do not have a significant effect on the level of poverty.